2008
DOI: 10.31899/rh4.1165
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the accessibility, acceptability and use of the IUD in Gujarat, India

Abstract: Despite the many advantages of the IUD as a method of family planning, it generally suffers from unpopularity worldwide, with the exception of a few countries like China, Egypt, Mexico and Turkey. The scenario in India is the same, with less than two percent of currently women adopting the IUD as a method of contraception. The USAID-funded FRONTIERS Program of the Population Council, in collaboration with the Department of Health & Family Welfare, Government of Gujarat and the Center for Operations Research an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
1
7
1
Order By: Relevance
“…Though the current studies finding revealed that a higher percentage of women were aware of LARC, in comparison with other studies the awareness on IUCD was lower than a study which reported in Nigeria Copper T (70.8%), India (77%), and USA (79%) [15,24,25]. Women in Mekelle City, Northern Ethiopia…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Though the current studies finding revealed that a higher percentage of women were aware of LARC, in comparison with other studies the awareness on IUCD was lower than a study which reported in Nigeria Copper T (70.8%), India (77%), and USA (79%) [15,24,25]. Women in Mekelle City, Northern Ethiopia…”
Section: Discussioncontrasting
confidence: 88%
“…This study is Consistent with a study done in Ethiopia, India, Nigeria, Bangladesh, Benin and USA [15,19,21,[25][26][27] The limitation of this could be that it didn't include the qualitative part; due to this it was not possible to capture detail reasons from different angles for not accepting LARC. But, the attempt was made to make the questionnaire more comprehensive to capture detail variables.…”
Section: Discussionsupporting
confidence: 85%
“…The scenario in India is the same with less than two percent of currently women adopting the IUD as a method of contraception. (8) An integrated approach to male involvement is needed. Some studies supported school-based clinics as a venue to involve male adolescents in contraceptive decision making.…”
Section: Review Of Literaturementioning
confidence: 99%
“…One example is the intrauterine device (IUD), one of the most highly effective and long‐acting temporary contraceptive methods available . The method is considered highly acceptable to both users and providers and is available in several geographic settings, including Egypt, China, Mexico and Turkey . However, a recent survey in the USA revealed that many women have misperceptions about the device's safety and effectiveness; only one in five had accurate knowledge that the IUD was more effective than the pill .…”
Section: Informing Product Development By Understanding Social–behavimentioning
confidence: 99%
“…16 The method is considered highly acceptable to both users and providers and is available in several geographic settings, including Egypt, China, Mexico and Turkey. 13,17 However, a recent survey in the USA revealed that many women have misperceptions about the device's safety and effectiveness; only one in five had accurate knowledge that the IUD was more effective than the pill. 18 Providers themselves had misperceptions about the method.…”
Section: Informing Product Development By Understanding Social-behavimentioning
confidence: 99%